Intra-articular injection of chondrogenic induced bone marrow stem cells in a sheep model - Alfaqeh, Hamoud Hussein Mohammed; Idrus, Ruszymah; yahya, norhamdan; Chen, Hui Cheng; Saim, Aminuddin (2012)
In recent year, the use of bone marrow mesenchymal stem cells (BMSCs) implantation has provided an alternative treatment for osteoarthritis ( OA). The objective of this study is to determine whether or not an intra-articular injection of a single dose of autologus chondrogenic induced BMSCs could retard the progressive destruction of cartilage in a surgically induced osteoarthritis in a sheep. from our findings it is suggested that an intra-articular injection into OA knee joints of sheep with autologus bone marrow stem cells cultured in chondrogenic medium has possibility of retarding the progression of OA.